Sosialisasi Pemanfaatan E-Commerce Bersama Karang Taruna Pada Usaha Ibus, Sebagai Upaya Peningkatan Kesejahteraan Masyarakat Di Desa Sidingkat, Kabupaten Padang Lawas Utara - Nur Hidayah; Ahmad Fauzan; Mhd Irfan Ash; Muhammad Tabroni; Nurul Aini; Nur Haya; Nur Jannah; Nur Melinda; Sopiah Sopiah (Maeswara : Jurnal Riset Ilmu Manajemen dan Kewirausahaan, 2024)
Indonesia faces challenges and opportunities in the digital era, where industry becomes a threat if human resources do not have sufficient skills to support this change. The digital industry offers great benefits if people have sufficient skills to engage in it. Many entrepreneurs have emerged in the digital era, generating income through online businesses or e-commerce. The use of this industry can provide optimal benefits, especially because the needs of modern humans are fast-paced and practical. Even though many people use gadgets with an internet connection, being just a spectator without actively participating in the digital era can cause losses. Sidingkat Village, which is rich in natural resource potential, especially ibus plants, has not utilized the internet optimally for development and marketing. Karang Taruna youth in this village have free time that has not been used productively. The aim of this Real Work Lecture (KKN) is to develop marketing of ibus plants and provide an understanding of online marketing media to Karang Taruna youth. The method used is the Participation Action Research (PAR) approach, which aims to increase public awareness of the potential and problems they have, as well as providing solutions through change programs. Through this approach, it is hoped that young people can be more productive and use their free time more effectively in the digital era